Effect of Health educational intervention in the form of counseling on changes in anthropometric and biochemical parameters of type 2 diabetes mellitus - Stantić-Romić Dijana; Požar Hajnalka; Šumonja Sanja (Association of Nurses Technicians and Midwives, 2023)
Introduction: Diabetes is a significant public health problem. In Serbia, 12% of the population suffers dominantly from type 2 diabetes, the development of which is associated with an inadequate diet and lack of physical activity. The treatment of patients involves the application of diet therapy in combination with medical treatment. The aim of this paper is to evaluate the differences in anthropometric and biochemical parameters in patients with type 2 diabetes after the counseling work. Respondents and methods: The research was conducted as a retrospective evaluation study through the analysis of medical records of users of the Nutrition Counseling Service of the Public Health Institute of Subotica. The sample included 34 patients with type 2 diabetes, mostly women (71%). Results: The average body weight of the patients was 87.6 kg, waist circumference 105 cm, the average glycemima was 7.14 mmol/l, and the blood pressure level was 140/84 mmHg. After counseling, at the first control measurement 2-4 months after the first examination, the patients lost an average of 3 kg, the waist circumference decreased by an average of 2 cm, and the percentage of fat in the body decreased by 1.6%. There was a decrease in glycemia by 0.6 mmol/l and systolic blood pressure by 5 mmHg. Although the second control examination was attended by a much smaller number of patients, based on the results, it was observed that the average values of the observed parameters were significantly lower compared to the initial values (body mass decreased by 1 kg, waist circumference by 4 cm, glycemia level by an additional 1 mmol/l). Conclusion: Based on the results of the research, it can be concluded that after the counseling work, there was a significant improvement in the nutritional status and glycemia in patients with type 2 diabetes.